2001
DOI: 10.1159/000056264
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and the Temperament and Character Model of Personality

Abstract: Objective: In our study we explored the associations between alexithymia (Toronto Alexithymia Scale 20, TAS-20) and the dimensions and subscales of Cloninger’s theoretically based and empirically validated psychobiological model of personality to further clarify the relationship between alexithymia and personality traits. Methods: Psychiatric in- and outpatients (n = 254) were investigated with the TAS-20, the Temperament and Character Inventory (TCI) and the Symptom Check List SCL-90-R to control for the seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 25 publications
6
54
1
3
Order By: Relevance
“…To our knowledge the present study is the first to investigate this relationship in a sample of alcoholdependent subjects. The present results supported the findings of Grabe et al, who studied a more heterogeneous sample of psychiatric inpatients and outpatients, 24 and the present results were consistent with the general view that alexithymia is not represented by one single personality dimension or subscale but is best explained by a mixture of different traits within Cloninger's temperament and character model of personality.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…To our knowledge the present study is the first to investigate this relationship in a sample of alcoholdependent subjects. The present results supported the findings of Grabe et al, who studied a more heterogeneous sample of psychiatric inpatients and outpatients, 24 and the present results were consistent with the general view that alexithymia is not represented by one single personality dimension or subscale but is best explained by a mixture of different traits within Cloninger's temperament and character model of personality.…”
Section: Discussionsupporting
confidence: 93%
“…Character dimensions selfdirectedness include acceptance of responsibility for one's own choices, identification of individually valued goals and purposes, development of skills and confidence in solving problems, and selfacceptance. 34 Instead of low reward dependence found in the study by Grabe et al, 24 we found selftranscendence as an independent predictor for alexithymia in the present sample. Character dimension of self-transcendence is described as selfforgetfulness, transpersonal identification, and spiritual acceptance.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Its absolute and relative stability in log-term follow-up (up to 11 years) has been reported high (44). Alexithymia is associated with different personality disorders (45,46), particularly with cluster B (47,48). In one study, just its affective aspect (41), and in the others, both of its affective and cognitive aspects are associated with personality disorders (47).…”
Section: Introductionmentioning
confidence: 97%